2021
DOI: 10.3390/ijerph18094862
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of the Combination of High-Intensity Interval Training with 3D-Multiple Object Tracking Task on Perceptual-Cognitive Performance: A Randomized Controlled Intervention Trial

Abstract: The ability to process goal-related visual information while ignoring goal-irrelevant information is essential for the human attention system. The study aimed to investigate how perceptual–cognitive performance was affected during high-intensity interval training (HIIT) using a 3D-multiple object tracking (3D-MOT) task called Neurotracker (NT). In an experimental design, 42 healthy adults (age M = 23.3 SD = 2.94, VO2max 52.8 ± 5.66 mL·kg−1·min−1) were randomly assigned to an intervention (HIIT + NT, NT, HIIT) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 60 publications
1
5
1
Order By: Relevance
“…It might be attributed to the fact that ordinary college students do not have the same soccer experience or training. A recent study used a 3D-MOT task in high-intensity interval training (HIIT) to explore the effect on perceptual-cognitive performance and reported that the combination training resulted in task-specific benefits, which confirms our findings ( Park et al, 2021 ). Romeas et al (2016) reported that long-term MOT training improves athletic performance and decision-making ability of soccer players.…”
Section: Discussionsupporting
confidence: 87%
“…It might be attributed to the fact that ordinary college students do not have the same soccer experience or training. A recent study used a 3D-MOT task in high-intensity interval training (HIIT) to explore the effect on perceptual-cognitive performance and reported that the combination training resulted in task-specific benefits, which confirms our findings ( Park et al, 2021 ). Romeas et al (2016) reported that long-term MOT training improves athletic performance and decision-making ability of soccer players.…”
Section: Discussionsupporting
confidence: 87%
“…Although most 3D-MOT studies used only the speed threshold as an indicator for performance (Park et al, 2021), we also analyzed the score of the fastest trial, considering that, together, these parameters could give a broader response regarding mental fatigue. However, none of these parameters were affected by mental fatigue inducement.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term MOT training positively affects motor stability and improves landing movement. It has been used for optokinetic simulation training, which possibly improved posture stability in dual tasks [ 2 , 37 ]. Therefore, much more training-related research needs to be conducted in this field in specific populations for robust training recommendations.…”
Section: Discussionmentioning
confidence: 99%